Transjugular intrahepatic portosystemic shunt with gastric vein embolization in liver cirrhosis - V. I. Korobka; Yu. V. Khoronko; V. D. Pasechnikov; R. V. Korobka; E. S. Pak; M. V. Malevanny; D. V. Pasechnikov; I. A. Ashimov (Вестник трансплантологии и искусственных органов, 2024)
Objective: to determine the predictors and risk of recurrent bleeding after implantation of a transjugular intrahepatic portosystemic shunt (TIPS) combined with selective gastric vein embolization in patients with decompensated cirrhosis awaiting liver transplantation (LT).Materials and methods. A comparative retrospective study was performed in 54 patients waitlisted for LT between 2017 and 2023, who suffered recurrent variceal hemorrhage after secondary prophylaxis of bleeding prior to inclusion in the study. Demographic, clinical and laboratory parameters, clinical indices, hepatic encephalopathy, severity of ascites, degree of varices, manometric study before and after TIPS implantation with gastric vein embolization, with calculation of portal pressure gradient in patients with (n = 16) and without rebleeding (n = 38), were analyzed. The proportions of patients were compared using the Kaplan–Meier method with determination of the logarithmic test (Log-Rank). Cumulative risks were estimated by means of univariate and multivariate analysis of the Cox proportional hazards model.Results. Within 30 weeks from the date of TIPS combined with gastric vein embolization, 16 of 54 patients (29.6%) developed rebleeding. The following risk factors were identified: age, hemoglobin level, white blood cell count, platelet count, creatinine level, severity of ascites, and mean portal pressure gradient after TIPS implantation. It was found that the proportion of patients without bleeding was significantly higher in patients with portal pressure gradient ≤10 mmHg than in patients with this index >10 mmHg (Log Rank = 0.029). The following independent predictors of recurrent hemorrhage were determined: severity of ascites, shunt thrombosis, portal pressure gradient after TIPS implantation, portal pressure gradient after TIPS implantation <30% of the basal level. It has been shown that the risk of recurrent bleeding at portal pressure gradient >10 mmHg progressively increases and reaches maximum values (HR = 1.713) in patients who underwent TIPS combined with gastric vein embolization between 32 and 40 weeks from the time of surgery, while it is absent at portal pressure gradient ≤10 mmHg.